Meta-analysis on the fatty acid composition of edible insects as a sustainable food and feed - Palupi, Eny; Nasir, Syifa Q.; Jayanegara, Anuraga; Susanto, Irwan; Ismail, Amin; Iwansyah, Ade Chandra; Setiawan, Budi; Sulaeman, Ahmad; M. Damanik, M. Rizal; Filianty, Fitry (Elsevier, 2025)
Edible insects align with multiple SDGs by offering sustainable solutions for zero hunger, food security, environmental conservation, health and economic development. Further assessment on their benefits might support wider utilization. The current work intended to elucidate the composition of fatty acids from the top 10 most researched edible insects using meta-analysis. A total of 222 articles was chosen and analyzed using a mixed-effects model and Hedges' d effect size. The observed parameters were 25 short- and medium-chain fatty acids, and 17 long-chain fatty acids. Further evaluation of the fatty acids content compared to beef was also performed. Mealworm, Mulberry silkworm, and Long-horned grasshopper were found to contain the highest levels of unsaturated fatty acids (73.4, 68.6 and 63.7 % of total lipids, respectively). The Mulberry silkworm found to have the highest omega-3 content (13.7 % of total lipids). Compared to beef, some edible insects seem promising for providing nutritious fatty acids. Moreover, these favorable content of lauric and myristic acids provide some expected advantages for further utilization as a feed, which produces more nutritious livestock with lower greenhouse gas emissions. Further research is needed to enhance the promotion of locally edible insects as viable sources of nutritious food and feed.